The Genealogy of Ali Mustafa Yaqub’s Hadith Understanding - Fatihunnada Fatihunnada; Hasan Basri Salim (AJIS: Academic Journal of Islamic Studies, 2021)
Ali Mustafa is an Indonesian hadith expert who has had a significant influence on the development of hadith studies in Indonesia in term of the study of hadith authenticity and the study of hadith understanding. This article explores Ali Mustafa's genealogy of understanding, method of understanding, and academic experiences during his education in Indonesia and Saudi Arabia. The data sources for this paper were Ali Mustafa's work entitled Female Imam, The Meeting Point of Wahabi-NU, and Islam is not only for Muslims. Through text analysis method with a genealogical approach, it can be described that Ali Mustafa's understanding of Genealogy was strongly influenced by several sources such as NU, Wahabi, Occidentalism, and the understanding of classical scholars. Ali Mustafa understood the hadith with the textual method first, then he used contextual method if the textual method could not be used to understand the hadith. The influence of Ali Mustafa's education in Indonesia through Islamic boarding schools was stronger than his educational experience in Saudi Arabia